Dearomative Dual Functionalization of Aryl Iodanes. (15th October 2019) - Zhao, Weizhao; Huang, Xin; Zhan, Yaling; Zhang, Qifeng; Li, Dongyang; Zhang, Yage; Kong, Lichun; Peng, Bo
Abstract: Herein we describe the dearomatization of aryl iodanes through an unprecedented "rearrangement/addition" sequence. The process consists of two stages. First, a rapid [3, 3] sigmatropic rearrangement of the aryl iodane with an α‐stannyl nitrile affords a highly electrophilic dearomatized intermediate at −78 °C. A low‐temperature rearrangement then enables the unstable dearomatized species to be trapped in situ with various nucleophiles. As a consequence, the reaction not only breaks the aromaticity of the aryl iodane but also sequentially installs two different functional groups, thus resulting in a polysubstituted alicyclic product. Abstract : Platz für zwei : Der Erfolg einer neuartigen Umlagerungs‐/Additionssequenz zur Dearomatisierung von Aryliodanen basiert auf einer schnellen Umlagerung (−78 °C, 10 min), die den Abfang instabiler dearomatisierter Zwischenprodukte mit einer Reihe von Nukleophilen bei tiefer Temperatur ermöglicht (siehe Schema).